Le conflit renaissant de la figure et de l’abstraction dans Labyrinthe, journal mensuel des Lettres et des Arts (octobre 1944-décembre 1946) - Blandine Delhaye (Les Cahiers de l'École du Louvre)
Labyrinthe, journal mensuel des Lettres et des Arts, edited by Albert Skira, comprised twenty-three issues published between 15 October 1944 and December 1946. Literature and the fine arts were the subjects of the great majority of the articles published in the review. Skira called on a few friends and several other collaborators to write the articles on art. The critics published in Labyrinthe were “occasional” reviewers or “professionals” such as Pierre Courthion, René Huyghe and Germain Bazin. Those who most assiduously frequented the editorial office in the Place du Molard in Geneva and took part in the conception of the journal were Swiss poet and painter Roger Montandon, Genevan philosopher Jean Starobinski, and artists Giacometti, Balthus and Brassaï. All the articles by these collaborators, permanently fluctuating between tradition and avant-garde, more or less reflect the artistic events of the period. We will see, on the one hand, how and why Balthus participated in the conception of an article by Pierre Courthion on Konrad Witz; on the other, we will attempt to grasp the extent to which the dispute between “figurative” and “non-figurative” art is expounded in the journal. Aware that the built heritage of which he was the trustee was of public interest, Louis-Joseph Guyot devoted himself to the promotion and conservation of the Dourdan past. He was one of the local, private actors, working in the shadow of official institutions, whose name has not gone down in history; and yet his work was far from insignificant. This article comprehends the logic of his undertaking and also aims to communicate the scope of an individual action that was part of the growing awareness of cultural heritage in the nineteenth century.